Hydroalcoholic Extract of Scrophularia Striata Attenuates Hypertrophic Scar, Suppresses Collagen Synthesis, and Stimulates MMP2 and 9 Gene Expression in Rabbit Ear Model - Hatam Zarei; Pari Tamri; Sara Soleimani Asl; Meysam Soleimani; Shirin Moradkhani (Korean Pharmacopuncture Institute, 2022)
Objectives: Hypertrophic scars (HSs) are caused by abnormal wound healing. To date, no standard treatment has been made available for HSs. Scrophularia striata has been reported to accelerate wound healing and has the potential to prevent HS formation. In this study, we investigated the anti-scarring effects of S. striata extract (SSE) in a rabbit ear model of scarring.Methods : In this study, New Zealand white rabbit (weight: 2.3-2.5 kg) were used. In the prevention phase of the study, three test groups received 5%, 10%, and 15% ointments of SSE in the Eucerin base, the fourth group received Eucerin, and the fifth group received no treatment. The samples were obtained on day 35 after wounding. In the treatment phase of the study, the test groups received an intralesional injection of SSE (5%, 10%, and 15%), the fourth group received an intralesional injection of triamcinolone, the fifth group received a solvent (injection vehicle), and the sixth group received no treatment. To evaluate the anti-scarring effects of SSE, the scar elevation index (SEI), epidermis thickness index (ETI), collagen deposition, and MMP2 and MMP9 gene expression were evaluated.Results : A significant reduction in SEI, ETI, and collagen deposition was noted in animals treated with SSE compared with the control groups. In addition, topical SSE stimulated MMP2 and MMP9 gene expression.Conclusion : The findings of this study demonstrate the potential for SSE in the prevention and treatment of HS. SSE could be prepared as an appropriate formulation to treat wounds and prevent abnormal scarring.